2017
DOI: 10.4102/jsava.v88i0.1457
|View full text |Cite
|
Sign up to set email alerts
|

A study of the incidence of milk fever in Jersey and Holstein cows at a dairy farm in Beatrice, Zimbabwe

Abstract: A 3-year prospective study investigated the incidence of milk fever in Jersey and Holstein cows at a commercial dairy farm in Beatrice, Zimbabwe. The overall incidence of milk fever at the farm was 7.98%. Incidence of milk fever in Jerseys (14.78%) was significantly higher (p < 0.05) than that in Holsteins (4.82%). Incidence of milk fever in Jerseys beyond their fourth parity (24.85%) was significantly higher (p < 0.05) than that in Jerseys in their second (5.90%), third (6.49%) and fourth (8.73%) parities. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
4
1
Order By: Relevance
“…Lean et al (2006) demonstrated that HC incidence is 2.25 times higher in Jersey cows than in Holstein cows. Similar results were reported by Chiwome et al (2017) on HC incidence in Jersey and Holsteins cows (14.78% and 4.82%, respectively). Despite several studies having described HC incidence among breeds, the mechanism involved in these differences remains unclear.…”
Section: Calcium Regulation In Dairy Cows and Hypocalcemia During Thesupporting
confidence: 89%
See 1 more Smart Citation
“…Lean et al (2006) demonstrated that HC incidence is 2.25 times higher in Jersey cows than in Holstein cows. Similar results were reported by Chiwome et al (2017) on HC incidence in Jersey and Holsteins cows (14.78% and 4.82%, respectively). Despite several studies having described HC incidence among breeds, the mechanism involved in these differences remains unclear.…”
Section: Calcium Regulation In Dairy Cows and Hypocalcemia During Thesupporting
confidence: 89%
“…The relative amount of intestinal calcitriol receptors in Jersey cows compared to Holsteins cows may affect the amount of calcium that can be absorbed in the intestine, which could be a potential explanation for the differences in HC susceptibility between breeds. It has also been suggested that differences in HC incidence between Jerseys and Holsteins may be related to the amount of milk produced by kilogram of BW (Blake et al, 1986;Chiwome et al, 2017), which is higher in Jerseys (average BW = 454 kg; average milk production = 31.7 kg/day) compared to Holsteins (average BW = 680 kg; average milk production = 35 kg/day) (Capper and Cady, 2012). However, not only the relation between milk yield and BW, but milk yield alone appears to be positively correlated with HC incidence in dairy cows.…”
Section: Calcium Regulation In Dairy Cows and Hypocalcemia During Thementioning
confidence: 99%
“…This type of variation was supported by the result observed in the 135 controlled trials from the meta-analysis data set used by [17], for which the mean incidence was 21% with a range of 0-83%. It was however, slightly lower than 8% reported by [18] from Zimbabwe. The prevalence of this study was moderately higher than the result reported in American 3.…”
Section: Discussioncontrasting
confidence: 63%
“…However, it is difficult to reunite these variations given that Ethiopian herds produce less milk than Western herds. The frequency of metabolic disorders maybe influenced by climatic conditions [18]. The variation in the extent of UV radiation, regular evaporation rate and the variation between maximum and minimum ambient temperature may meaningfully disturb the occurrence of milk fever [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Hypocalcemia is divided into subclinical (total calcium concentration of 1.4 to 2.0 mmol/L) or clinical (total calcium concentration < 1.4 mmol/L), accompanied by mental restlessness, anorexia, mild paralysis, and even death. Compared to primiparous cows, later parity cows are relatively more susceptible to developing clinical symptoms of milk fever [132,133]. Hypocalcemia is a risk factor for causing ketosis, displaced abomasum, mastitis, retained placenta, and uterine prolapse [134] and thereby presents a greater chance of culling.…”
Section: The Impact Of Hypocalcemia (Milk Fever) On Reproductive Efficiency Of Dairy Cattlementioning
confidence: 99%